2022
DOI: 10.1021/jacs.2c08760
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Scale Enantioselective Synthesis of (+)-Lucidumone

Abstract: The first enantioselective total synthesis of (+)-lucidumone is described through a 13-step synthetic pathway (longest linear sequence). The key steps involve the formation of a bridged bicyclic lactone by an enantioselective inverse-electron-demand Diels–Alder cycloaddition, C–O bond formation to assemble two fragments, and a one-pot retro-[4 + 2]/[4 + 2] cycloaddition cascade. The synthesis is scalable, and more than one gram of natural product was synthesized in one batch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The unique structure and intriguing bioactivity inspired us to synthesize 1 . The total synthesis of 1 has previously been reported only by Torre‘s group [2] . In Torre's report, 1 was synthesized on gram‐scale through repeated Diels–Alder cycloadditions.…”
Section: Methodsmentioning
confidence: 99%
“…The unique structure and intriguing bioactivity inspired us to synthesize 1 . The total synthesis of 1 has previously been reported only by Torre‘s group [2] . In Torre's report, 1 was synthesized on gram‐scale through repeated Diels–Alder cycloadditions.…”
Section: Methodsmentioning
confidence: 99%
“…The Tang group recently demonstrated that side arms on the bisoxazoline framework have a marked influence on both reactivity and stereocontrol. 29 This strategy was subsequently employed successfully by us [20][21][22] and by de la Torre and co-workers [25][26] in the development of enantioselective IEDDA reactions of 2-pyrones. Inspired by these works, modifications of L6 by installing only one example 91%, 84% ee by Gademann [28] O O PhSe…”
Section: Letter Synlettmentioning
confidence: 99%
“…Therefore, the development of an efficient asymmetric catalytic system to promote this reaction under mild reaction conditions is highly desirable. Although great achievements have been made very recently for the development of enantioselective IEDDA reactions of 2-pyrones, [18][19][20][21][22][23][24][25][26] the reaction using a cis-phenyl vinyl selenide as the dienophile remains elusive. Only two related examples have been reported.…”
mentioning
confidence: 99%
See 2 more Smart Citations